2015
DOI: 10.1007/s11738-015-1971-z
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous hydrogen sulfide regulated by calcium is involved in thermotolerance in tobacco Nicotiana tabacum L. suspension cell cultures

Abstract: Calcium (Ca 2? )/calmodulin (CaM), a core component of calcium messenger system, is a multiple second messenger that is involved in multiple stress tolerance including heat tolerance in plants, hydrogen sulfide (H 2 S) is fast emerging similar functions, but Ca 2? and H 2 S crosstalk in the acquisition of thermotolerance is not completely understood. In this article, Ca 2? and CaM activated the activity of cysteine desulfhydrase (L-DES), followed by inducing endogenous H 2 S accumulation in tobacco suspension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 45 publications
1
12
0
3
Order By: Relevance
“…Under heat stress, antioxidant enzymes activities, antioxidants contents and the ratio of the reduced antioxidants to total antioxidants in control and treated seedlings all decreased, but NaHS-treated seedlings maintained higher antioxidant enzymes activities and antioxidants levels as well as reduced antioxidants/total antioxidants ratio (Li Z.G. et al, 2014), similar results also were found in tobacco cells (Li et al, 2015). In addition, NaHS pretreatment significantly increased the survival percentage of tobacco cells under heat stress and regrowth ability after heat stress, alleviated a decrease in vitality of cells and an increase in electrolyte leakage and MDA accumulation (Li et al, 2012b).…”
Section: H2s-induced Cross-adaptationsupporting
confidence: 57%
“…Under heat stress, antioxidant enzymes activities, antioxidants contents and the ratio of the reduced antioxidants to total antioxidants in control and treated seedlings all decreased, but NaHS-treated seedlings maintained higher antioxidant enzymes activities and antioxidants levels as well as reduced antioxidants/total antioxidants ratio (Li Z.G. et al, 2014), similar results also were found in tobacco cells (Li et al, 2015). In addition, NaHS pretreatment significantly increased the survival percentage of tobacco cells under heat stress and regrowth ability after heat stress, alleviated a decrease in vitality of cells and an increase in electrolyte leakage and MDA accumulation (Li et al, 2012b).…”
Section: H2s-induced Cross-adaptationsupporting
confidence: 57%
“…Similar phenomena were observed in plants. Many external factors, such as damage (Zhang et al 2011 ), hormone induction (Xie et al 2014a ), and lack of light (Hu et al 2015a ; Li et al 2015e ), can lead to early senescence in plants. Besides, rhythm, climate and seasonal changes also induce the natural aging of plants.…”
Section: H 2 S Contributes To Plant Growth and Devmentioning
confidence: 99%
“…For example, H 2 S treatment alleviated dark-promoted senescence in broccoli florets by sustaining higher activities of GPX, APX, CAT and GR and lower activities of lipoxygenase (LOX), PPO, PAL and protease (Li et al 2014b , 2015e ). Similarly, NaHS treatment on aleurone tissue led to higher transcript levels of the antioxidant genes HvSOD1 , HvAPX , HvCAT1 and HvCAT2 and lower transcript levels of HvLOX and cysteine protease genes HvEPA and HvCP3-31 (Zhang et al 2015a ).…”
Section: H 2 S Contributes To Plant Growth and Devmentioning
confidence: 99%
“…All of these increases induced by Ca 2+ /CaM, in DES1 activity, H 2 S content, and heat tolerance are enhanced by the H 2 S donor NaHS or weakened by H 2 S synthesis inhibitors or an H 2 S scavenger. Therefore, during the heat stress response process, the H 2 S and Ca 2+ signals may be interdependent [ 112 ].…”
Section: Mechanism By Which H 2 S Regulates Plamentioning
confidence: 99%